2020
DOI: 10.1093/infdis/jiaa401
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Rifabutin and Rifapentine to Treat Methicillin-Resistant Staphylococcus aureus in a Rat Model of Foreign Body Osteomyelitis

Abstract: Abstract Background Due to patient intolerance or drug interactions, alternative agents to rifampin are needed for management of staphylococcal periprosthetic joint infection (PJI). Here, we evaluated rifabutin, rifapentine and rifampin, with and without vancomycin, in a rat model of foreign body osteomyelitis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Addition of rifampin is recommended in some scenarios due to its activity against staphylococcal biofilms (41,42) and intracellular staphylococci (42), and ability to penetrate bone tissue (43). We have shown in multiple studies that rifampin is active in orthopedic MRSA rat models; however, we have observed several instances of selection of rifampin resistance with rifampin monotherapy (25,29,30), including three animals in the current study. The rate of reported rifampin resistance varies from study to study, both in our work and in the literature, varying with rifampin dose and model type.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Addition of rifampin is recommended in some scenarios due to its activity against staphylococcal biofilms (41,42) and intracellular staphylococci (42), and ability to penetrate bone tissue (43). We have shown in multiple studies that rifampin is active in orthopedic MRSA rat models; however, we have observed several instances of selection of rifampin resistance with rifampin monotherapy (25,29,30), including three animals in the current study. The rate of reported rifampin resistance varies from study to study, both in our work and in the literature, varying with rifampin dose and model type.…”
Section: Discussionmentioning
confidence: 60%
“…A vancomycin AUC/MIC ratio between 400 and 600 is recommended for humans ( 26 ); with a MIC of 1 μg/ml, the vancomycin AUC/MIC was 368, slightly lower than this goal range. However, higher doses in rats have been shown to cause toxicity ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampin is an antibiotic with antibiofilm activity used in the management of staphylococcal periprosthetic joint infection (PJI) with irrigation and debridement with component retention (IDCR) ( 1 , 2 ); some patients are unable to receive rifampin due to drug interactions or intolerance. We recently showed that rifabutin and rifapentine, which have more favorable drug interaction/side effect profiles than rifampin, have in vitro activity against planktonic and biofilm states of rifampin-susceptible PJI-associated staphylococci ( 3 ), and that these rifamycins are as active as rifampin in combination therapy regimens in experimental rat Staphylococcus aureus foreign body osteomyelitis ( 4 ). After staphylococci, streptococci and enterococci combined are the most common causes of PJI, accounting for up to 20% of cases ( 5 8 ).…”
Section: Observationmentioning
confidence: 99%
“…Rifampin exhibits potent induction of multiple cytochrome P450 (CYP450) enzymes and P-glycoprotein (P-gp) transport system proteins, which causes interactions with commonly prescribed medications that may warrant dose adjustment or switch to another therapeutic agent altogether during concomitant rifampin therapy ( 6 , 8 ). Rifabutin, though used less commonly than rifampin in clinical settings, is another rifamycin that exhibits potent in vitro antistaphylococcal activity as well as fewer CYP450 enzyme interactions and no induction of P-gp proteins ( 5 , 6 , 9 ). Recently, Tuloup et al studied a model-based analysis comparing rifampin and rifabutin drug-drug interaction profiles and concluded that interactions caused by rifampin were twice as potent as those caused by rifabutin ( 10 ).…”
Section: Introductionmentioning
confidence: 99%